Исследование иерархической структуры углей донецкого бассейна методом малоуглового рассеяния нейтронов - Василенко, Т.А.; Кириллов, А.К.; Соболев, В.В.; Дорошкевич, А.С.; Пронский, Е.А. (Физико-технические проблемы горного производства, 2018)
Целью исследования является определение фрактальных характеристик иерархической структуры ископаемых углей с помощью такого неразрушающего метода, как малоугловое рассеяние тепловых нейтронов, позволяющего изучать структуру в объеме образцов.
В работе определены фрактальные размерности и получены их корреляционные связи с удельной поверхностью порового пространства, степенью углефикации, глубиной залегания и склонностью пластов к выбросам угля и газа для углей Донецкого угольного бассейна. Полученные фрактальные размерности и удельные поверхности дают представление о полной пористости в отличие от метода низкотемпературной адсорбции азота, характеризующего только открытую пористость.
Впервые показано, что структура углей выбросоопасных пластов характеризуется поверхностным фракталом Df с размерностью, близкой к значениям 2,9 – 3,0 или массовым фракталом, который образован конгломератами различных минеральных включений, содержащих железо и серу. В угрожаемых пластах структура угля характеризуется более «гладкими» поверхностями порового пространства при значениях Df < 2,9 и повышенным содержанием кремния и алюминия. Метою дослідження є визначення фрактальних характеристик ієрархічної структури викопного вугілля за допомогою такого неруйнівного методу, як малокутове розсіювання теплових нейтронів, що дозволяє вивчати структуру в об'ємі зразків.
В роботі визначені фрактальні розмірності і отримані їх кореляційні зв'язки з питомою поверхнею порового простору, ступенем вуглефікації, глибиною залягання і схильністю пластів до викидів вугілля і газу для вугілля Донецького вугільного басейну. Отримані фрактальні розмірності і питомі поверхні дають уявлення про повну пористість на відміну від методу низькотемпературної адсорбції азоту, що характеризує тільки відкриту пористість.
Вперше показано, що структура вугілля викидонебезпечних пластів характеризується поверхневим фракталом Df з розмірністю, близькою до значень 2,9 – 3,0 або масовим фракталом, який утворений конгломератами різних мінеральних включень, що містять залізо і сірку. У загрозливих пластах структура вугілля характеризується більш «гладкими» поверхнями порового простору при значеннях Df < 2,9 і підвищеним вмістом кремнію і алюмінію. The investigation of fractal structures in the physics of condensed matter is an urgent task. An example of a geometric fractal is the complex hierarchical organization of the pore space of fossil coals, represented as fractal clusters containing elements of different scales. The determination of the fractal dimension of such objects makes it possible to explain the dependence of the physical and mechanical characteristics of the coals under external influences.
The aim of the study is the determination of the fractal characteristics of hierarchical structure of fossil coals by means of a non-destructive method such as small-angle scattering of thermal neutrons, which makes it possible to study the structure in the volume of samples.
Fractal dimensions and their correlation links with the specific surface of the pore space, the degree of coalification, the depth of coal seam and with the propensity of the seam to coal and gas outbursts for coals of the Donetsk coal basin are determined. The resulting fractal dimensions and specific surfaces gives the total porosity, in contrast to the method of low-temperature adsorption of nitrogen, which characterizes open porosity only.
The photomicrographs obtained with the scanning electron microscope made it possible to conclude that the structure of the coal of the outburst hazardous layers is characterized by a surface fractal Df with a dimension close to 2,9–3,0 or by the mass fractal that is formed by conglomerates of various mineral inclusions containing iron and sulfur. In threatened seams, the coal structure is characterized by more "smooth" pore space surfaces at Df < 2,9 and by the higher content of silicon and aluminum.